2011
DOI: 10.1016/j.jcrs.2010.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Vector analysis of astigmatic changes after cataract surgery with toric intraocular lens implantation

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 57 publications
8
21
0
Order By: Relevance
“…The postoperative manifest cylinder refraction at 6 months (means ± standard deviation) was -0.74 D ± 0.26 D in the LRI group and -0.62 D ± 0.17 D in the toric IOL group, values consistent with those reported in the current literature (-0.71 D ± 0.42 D (13) and -0.94 D ± 0.40 D (23) ). These refractions were consistently lower than the intended astigmatism within each group and showed comparable outcomes between groups (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…The postoperative manifest cylinder refraction at 6 months (means ± standard deviation) was -0.74 D ± 0.26 D in the LRI group and -0.62 D ± 0.17 D in the toric IOL group, values consistent with those reported in the current literature (-0.71 D ± 0.42 D (13) and -0.94 D ± 0.40 D (23) ). These refractions were consistently lower than the intended astigmatism within each group and showed comparable outcomes between groups (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…(18,19) Differences between pre and postoperative refractive cylinders were statistically significant within each group throughout the follow up period (p value = 0.00). Between groups, however, they were not (p value > 0.05).…”
Section: Discussionmentioning
confidence: 92%
“…This confirms that the rotational stability of the evaluated bitoric IOL was good in most cases, which is consistent with the level of rotational stability reported for other toric IOLs. 8,18,19 Mendicute et al 8 reported a mean IOL rotation of 3.63° in eyes implanted with the Acrysof toric IOL, with 96% of eyes showing an IOL rotation of 10° or less. With the same type of toric IOL, Alió et al 18 obtained a mean value of IOL rotation of 3.35° ± 3.56°.…”
Section: Discussionmentioning
confidence: 99%
“…8,18,19 Mendicute et al 8 reported a mean IOL rotation of 3.63° in eyes implanted with the Acrysof toric IOL, with 96% of eyes showing an IOL rotation of 10° or less. With the same type of toric IOL, Alió et al 18 obtained a mean value of IOL rotation of 3.35° ± 3.56°. Sheppard et al 5 found a mean absolute IOL misalignment from the intended axis of 3.4° (range: 0° to 12°) in a sample of eyes implanted with the Tecnis toric IOL (Abbott Medical Optics, Inc., …”
Section: Discussionmentioning
confidence: 99%